Ground Motion and Air Overpressure Study. (1998) - Sharp, Michael K.; Yule, Donald E.
Abstract : A seismic attenuation and air overpressure study was conducted to determine the attenuation of explosion induced ground motions and air overpressures as a function of distance from shallow subsurface detonated charges, and to derive parameters to predict blast effects at distances beyond the ordinance disposal facility boundary. A total of 210 explosive shots were monitored producing 2048 time histories of ground motions recorded in the vertical, radial, and transverse directions, in addition to recording air overpressures. The data were analyzed for peak particle velocities and peak air overpressures, then plotted versus scaled range. A best fit line was determined for the data to give average, 95% non-exceedance, and upper bound predictive equations which can be used in the disposal operations to avoid damage to adjacent structures.